(untitled) (Private Law, 2025)
This study aims to explain why third parties oppose the determination of land boundaries by the Head of the Praya District Court and to elucidate the considerations of the District Court in determining the boundaries of land owned by third parties not involved in previous litigation. This research employs a normative legal approach. The findings reveal that the third party filed a "derden verzet" (third-party opposition) because the opponent was greatly aggrieved by the infringement of their rights as the legitimate owner of the disputed land, as evidenced by Certificate of Ownership No. 610 of Mekarsari Village in the name of Yunita Yusuf, which was to be determined by the Praya District Court. Furthermore, the opponent was not involved as a party in the previous litigation. The legal considerations of the Praya District Court Judge in decision No. 77/Pdt.Bth/2019/PN.Pya were that the panel of judges rejected the opponent’s objection, considering it legally unfounded, and the opponent failed to substantiate their claim of ownership of the disputed land in the a quo case. However, in the determination case, the third party filing the "derden verzet" was able to prove that part of the determined land was rightfully theirs according to Certificate of Ownership No. 610 of Mekarsari Village in the name of Yunita Yusuf.